Isolation and Identification of Flavonoids with Aldose Reductase Inhibitory Activity from Petasites japonicus - Gu Lee, Dong; Ho Lee, Ki; Park, Kwang-Woo; Kyu Han, Chan; Ryu, Buom-Yong; Ju Cho, Eun; Lee, Sanghyun (Asian Journal of Chemistry, 2015)
The purpose of this study was to evaluate the therapeutic potential of naturally occurring aldose reductase inhibitors extracted from Petasites japonicus. Methanol extract and stepwise polarity fractions of P. japonicus leaves were tested for aldose reductase inhibition on rat lenes in vitro. Of these, the ethyl acetate (EtOAc) fraction exhibited aldose reductase inhibitory activity (IC50 value, 0.26 μM). Chromatography of the active EtOAc fraction led to the further isolation of four flavonoids, identified as kaempferol-3-O-(6"-acetyl)-b-D-glucoside (1), quercetin-3-O-(6"-acetyl)-b-D-glucoside (2), kaempferol-3-O-b-D-glucoside (3) and quercetin-3-O-b-D-glucoside (4). Compounds 1-4 exhibited high aldose reductase inhibitory activity, with IC50 values of 6.08, 3.46, 8.55 and 2.21 μM, respectively. Compounds 1 and 2 were isolated for the first time from this plant and compound 4 showed the highest aldose reductase inhibitory activity. These results suggest that compound 4 extracted from P. japonicus is a potent aldose reductase inhibitor and could be a useful lead compound in the development of a novel aldose reductase inhibitory agent against diabetic complications.